Reproduction and oxidative metabolism in the brooding sea star Anasterias antarctica (Lütken, 1957) - Perez, Analia Fernanda; Boy, Claudia Clementina; Calcagno, Javier Angel; Malanga, Gabriela Fabiana (Journal of Experimental Marine Biology and Ecology)
The oral-brooding sea star Anasterias antarctica is distributed on the coasts of South Patagonia and north of Antarctic Peninsula. This species is a potential predator of shellfish Mytilus chilensis, an important commercial resource for Beagle Channel region. The aims of this work were to study the variation in the gonad index (GI), to establish the brooding season, to determine the reproductive effort of both sexes, and to assess the concentration of liposoluble antioxidants and production of reactive oxygen species (ROS) in male and female gonads and embryos of A. antarctica during the year. Four samplingswere performed: three during the brooding season and one during the non-brooding season. Individuals sampled during the brooding season were assigned to one of the three groups: brooding females, non-brooding females, and males. Individuals sampled during the nonbrooding seasonwere assigned to one of the three groups: sexuallymature females, sexually non-mature females and males. Histological observations allowed determining that only females incubate the embryos on the oral surface for seven months. Males showed a strategy characteristic of broadcast spawners, whereas females spawned only a small number of eggs, as it is characteristic of brooders and as observed in other species of asteroids. Males show a significant increase in GI before spawning (from 1% to 15%) and then a marked decrease. During gametogenesis, testes showed a low level of β-carotene and high production of ROS. Between May and October; brooding and non-brooding females showed similar values of ROS production and concentration of antioxidants. Mature females had a significantly higher GI and lipid soluble antioxidant concentration than non-mature females. ROS production was higher in non-mature females. In A. antarctica embryos, ROS production increased and liposoluble antioxidant defenses decreased along development. The reproductive effort of males was about 25% lower than that of females, probably because of brooding costs. Gonadal ...